KNOWLEDGE SHARING BEHAVIOR GURU DITINJAU DARI TRANSFORMATIONAL LEADERSHIP DAN SELF-EFFICACY [TEACHERS’ KNOWLEDGE SHARING BEHAVIOR FROM TRANSFORMATIONAL LEADERSHIP AND SELF-EFFICACY’S PERSPECTIVE] - Judha Semal Irianto; Niko Sudibjo (Polyglot, 2019)
The changing context of the age and the characteristics of today's generation demand that the role of the teacher be more creative and innovative. A way to answer this need is to cultivate a knowledge sharing behavior in the school environment. There are many factors that can support the establishment of this knowledge sharing behavior, including transformational leadership and self-efficacy. This study aims to determine the effect of transformational leadership and self-efficacy on the knowledge sharing behavior of teachers. The research subjects were 112 teachers who teach in two locations of XYZ Private High School in West Jakarta which have the potential to develop knowledge sharing behavior. The design used in this study was correlational, using surveys to collect the data and then analyze using the PLS-SEM method. The results of this study showed that transformational leadership and self-efficacy affected knowledge sharing behavior positively.BAHASA INDONESIA ABSTRAK: Perubahan konteks zaman dan karakteristik generasi zaman sekarang menuntut peran guru yang semakin kreatif dan inovatif. Salah satu upaya untuk menjawab hal ini adalah dengan membudayakan perilaku knowledge sharing behavior di lingkungan sekolah. Ada banyak faktor yang dapat mendukung terbangunnya perilaku knowledge sharing behavior ini, di antaranya transformational leadership dan self-efficacy. Penelitian ini bertujuan untuk mengetahui pengaruh transformational leadership dan self-efficacy terhadap knowledge sharing behavior guru. Subjek penelitian adalah 112 guru yang mengajar di dua lokasi Sekolah Menengah Atas Swasta XYZ di Jakarta Barat yang memiliki potensi untuk membangun perilaku knowledge sharing behavior. Desain penelitian bersifat korelational, data diambil berdasarkan survey yang dianalisi dengan metode PLS-SEM. Hasil penelitian yang diperoleh memperlihatkan bahwa transformational leadership dan self-efficacy mempengaruhi knowledge sharing behavior secara positif.